RANCANG BANGUN PENDETEKSI KADAR BORAKS PADA LONTONG DENGAN METODE UJI TURMERIK MENGGUNAKAN SENSOR WARNA TCS3200 BERBASIS MIKROKONTROLER ARDUINO - E Rosdiana; V A Kusumaningtyas; Kurniawan, Mutiara Fadillah; F Rahman (Telkom University, 2024)
Lontong is a traditional Indonesian rice-based food that is wrapped and boiled until cooked. It has a relativel short shelf life at room temperature, typically lasting only 1 to 2 days before spoilage occurs. In an effort to prolong its shelf life, some individuals have illicitly used borax as a food additive, despite its prohibition due to serious health risks. This study presents the design and development of a borax detection device for lontong using a turmeric-based colorimetric test integrated with a TCS3200 color sensor and an Arduino UNO microcontroller. Samples were prepared with varying borax concentrations ranging from 0 g/g to 7 g/g. Turmeric paper was used as a reagent, which changes color from yellow to orange or brick red in the presence of borax. The TCS3200 sensor detects the color change and converts it into frequency signals, which are processed by the microcontroller. The estimated borax concentration is displayed on an LCD module. The system demonstrated detection reliability rates of 100%, 100%, 96%, 96%, 90%, 100%, 98%, and 96% corresponding to each borax concentration level.Key Words: borax, lontong, mikrokontroler, turmerik, sensor TCS3200.